Participation of a primary teacher in creation of conditions to freedom for students - Głowala, Agnieszka (Nauczyciel wczesnej edukacji wobec zmian społeczno-kulturowych, 2016)
The author embarks on freedom of student in breeding process. She defines freedom in two ways of human living: in personal way and way of social relations, emphasizing function of creative action in freedom also. She mentions that from the point of view of pedagogy, priority purpose is to answer the question: how to develop student’s freedom in order to make it an agent of his integral development, not degradation. That task implicates next question: how should we develop the need of freedom, support student to raise in his or her humanity using freedom. Limiting freedom of students integrally connects with their different reactions, from „silent agreement” to autonomy. The problem of freedom at school is also a media of negative appearances which have a role in personal development of human. Looking for a ways of breeding, the author emphasises that the main method is pedagogic dialogue with students which is based on united solving of axiological problems and judging own deeds. The author also includes results of surveys concerning sense of freedom in younger school age and implications resultant from them.